Influences of red blood cell and platelet counts on the distribution and elimination of crystalloid fluid - Robert G. Hahn (Medicina, 2017)
Background and objective: A high number of blood cells increases the viscosity of the blood. The present study explored whether variations in blood cell counts are relevant to the distribution and elimination of infused crystalloid fluid.Materials and methods: On three different occasions, 10 healthy male volunteers received an intravenous infusion of 25 mL/kg of Ringer's acetate, Ringer's lactate, and isotonic saline over 30 min. Blood hemoglobin and urinary excretion were monitored for 4 h and used as input in a two-volume kinetic model, using nonlinear mixed effects software. The covariates used in the kinetic model were red blood cell and platelet counts, the total leukocyte count, the use of isotonic saline, and the arterial pressure.Results: Red blood cell and platelet counts in the upper end of the normal range were associated with a decreased rate of distribution and redistribution of crystalloid fluid. Simulations showed that high counts were correlated with volume expansion of the peripheral (interstitial) fluid space, while the plasma volume was less affected. In contrast, the total leukocyte count had no influence on the distribution, redistribution, or elimination. The use of isotonic saline caused a transient reduction in the systolic arterial pressure (P < 0.05) and doubled the half-life of infused fluid in the body when compared to the two Ringer solutions. Isotonic saline did not decrease the serum potassium concentration, despite the fact that saline is potassium-free.Conclusions: High red blood cell and platelet counts are associated with peripheral accumulation of infused crystalloid fluid.